A composite hydrogel and a preparation method and application thereof
Patent Information
- Application Number
- CN202611409573.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-30
AI Technical Summary
然而,TGF-β1等蛋白类生长因子在体内环境中半衰期较短,易被酶解而快速失活,传统的直接给药方式难以在缺损部位维持有效的治疗浓度,反复注射则增加了感染风险和患者痛苦
[0015]一种所述制备方法制备得到的复合水凝胶的应用,所述复合水凝胶用于制备修复骨缺损的支架。
Smart Images

Figure CN122998477A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogel technology, and in particular to a composite hydrogel, its preparation method, and its application. Background Technology
[0002] Bone defects are a serious challenge in clinical practice, usually caused by severe trauma, resection of bone tumors, and infectious diseases, often leading to functional impairment and a significant decline in quality of life for patients. Although autologous bone transplantation and allogeneic bone transplantation are still the gold standard procedures for the clinical treatment of bone defects, problems such as donor site complications, limited sources, and potential immune rejection have greatly restricted their widespread application. Against this background, bone tissue engineering strategies have provided new ideas and solutions for the regeneration and repair of bone defects. An ideal artificial bone repair scaffold should have the following key characteristics: (1) excellent biocompatibility to support cell adhesion, proliferation, and differentiation; (2) biodegradability that matches the rate of new bone formation; (3) mechanical properties that are adapted to the bone defect area; and (4) good osteoconductivity and osteoinductive properties that can actively guide and promote new bone formation.
[0003] In bone regeneration, the extracellular matrix (ECM) plays an irreplaceable role. It not only serves as the physical scaffold for cell growth but also regulates cell fate through a complex signaling network, mediating the exchange of substances and information between newly formed and original tissues. In recent years, hydrogels have attracted widespread attention in the biomedical field due to their high water content, three-dimensional porous network structure, and physicochemical properties highly similar to natural ECM, and are widely recognized as ideal candidate materials for constructing bone tissue engineering scaffolds. Among them, GelMA, a chemically modified gelatin derivative, retains the natural arginine-glycine-aspartic acid (RGD) sequence and matrix metalloproteinase (MMP) degradation sites in gelatin molecules. It possesses excellent photocrosslinking properties and tunable mechanical properties, and has shown great potential in bone regeneration research. Hyaluronic acid (HA) is an important component of natural ECM, widely distributed in connective tissues such as bone, and exhibits good biocompatibility and biodegradability. After aldehyde modification, HA-CHO can undergo a Schiff base reaction with the free amino groups of gelatin molecules through its aldehyde groups, forming a dynamic covalent crosslinked network. This dynamic crosslinking strategy not only avoids the cytotoxicity that may result from traditional chemical crosslinking agents, but also endows hydrogels with self-healing and injectable properties. Therefore, combining the photocrosslinking network of GelMA with the dynamic Schiff base network of GelMA / HA-CHO holds promise for constructing a multi-crosslinked composite hydrogel system that combines excellent mechanical properties with a biomimetic microenvironment.
[0004] However, simple hydrogel matrices often lack sufficient bioactivity to efficiently induce bone defect regeneration and repair. Therefore, introducing suitable active ingredients into hydrogel systems to enhance their osteogenic activity is particularly important. Transforming growth factor-beta 1 (TGF-β1) is a growth factor with multiple biological functions, playing a core regulatory role in bone metabolism and bone regeneration. Studies have shown that TGF-β1 can promote the differentiation and chemotactic migration of mesenchymal stem cells towards osteoblasts and upregulate the expression of osteogenic-related markers such as alkaline phosphatase, osteopontin, and osteocalcin. However, protein growth factors such as TGF-β1 have a short half-life in the in vivo environment and are easily degraded by enzymes and rapidly inactivated. Traditional direct administration methods are difficult to maintain effective therapeutic concentrations at the defect site, and repeated injections increase the risk of infection and patient suffering. Therefore, developing delivery carriers that can sustain the release of TGF-β1 and maintain its bioactivity over a long period is a key step in achieving efficient and safe bone regeneration.
[0005] Carbon dots (CDs), as a new class of zero-dimensional carbon-based nanomaterials, have attracted much attention due to their excellent fluorescence properties, good water solubility, low cytotoxicity, and flexible preparation methods. In recent years, an increasing number of studies have found that carbon dots can be endowed with unique biological activities by selecting precursors containing specific functional groups. L-arginine (L-Arg) is a functional amino acid involved in various biological processes such as protein synthesis, angiogenesis, and immune regulation. Studies have shown that L-arginine, as an endogenous precursor of nitric oxide (NO), plays an important role in bone metabolism regulation by producing NO, which can promote osteoblast proliferation and differentiation through the NO signaling pathway and play a key regulatory role in bone development. Arg-CDs prepared using L-arginine as a precursor not only inherit many advantages of carbon dot nanomaterials but also hold promise for retaining the angiogenic activity and bioregulatory functions of L-arginine. As a novel material that combines the dual roles of nanodelivery carrier and bioactive component, it has unique application prospects in bone defect repair. Based on the above background, the present invention provides a method for preparing a composite hydrogel, the method for preparing the hydrogel, and its application. Summary of the Invention
[0006] In view of this, the present invention addresses the deficiencies of existing technologies, and its main objective is to provide a method for preparing a composite hydrogel, as well as its preparation method and applications. The present invention uses L-arginine as a raw material to prepare Arg-CDs via pyrolysis, and hyaluronic acid as a raw material to prepare HA-CHO via sodium periodate oxidation. Then, using GelMA and HA-CHO as matrices, a dual-network hydrogel is constructed through photocrosslinking and Schiff base reaction. The preparation method is simple to operate, with mild reaction conditions, and can achieve efficient loading and controlled release of Arg-CDs and TGF-β1, exhibiting good process repeatability and potential for large-scale production. The composite hydrogel of the present invention can serve as a candidate scaffold material for bone defect repair, especially suitable for the repair of critical-sized skull defects, and has good clinical application prospects and translational potential.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a composite hydrogel includes the following steps: Preparation of S1 and Arg-CDs: Arg-CDs were prepared by pyrolysis using L-arginine as a raw material; Preparation of S2 and HA-CHO: HA-CHO was obtained by oxidizing hyaluronic acid with sodium periodate, terminating the reaction, dialysis and freeze-drying. S3. Preparation of Arg-CDs / GelMA / HA-CHO composite hydrogel: S31. Preparation of precursor solution; S32. Mixing of nanocomposite system; S33. Photocrosslinking to form gel; S34. Dynamic covalent crosslinking.
[0008] As a preferred embodiment: Step S1 specifically involves: heat-treating the arginine powder, cooling it, dissolving the residue in ultrapure water, sonicating the resulting turbid liquid, centrifuging it, and dialysis it; freezing and vacuum drying the dialysis solution to obtain powdered Arg-CDs.
[0009] As a preferred embodiment: the heat treatment conditions in step S1 are: calcination temperature 240℃, heating rate 4℃ / min, pyrolysis time 3 h; the centrifugation conditions are: centrifugation at 15,000 r / min for 30 min at room temperature; and the obtained powdered Arg-CDs are stored at 4℃.
[0010] As a preferred embodiment: Step S2 specifically involves: dissolving HA in deionized water, adding sodium periodate to the solution, and stirring the reaction for 2-3 hours; after the reaction is completed, adding ethylene glycol to terminate the reaction; and after dialysis, freeze-drying the solution to obtain HA-CHO.
[0011] As a preferred embodiment: Step S31, the preparation of the precursor solution, specifically involves adding methacrylamide gelatin (GeMA) and aldehyde-modified hyaluronic acid (HA-CHO) to a phosphate buffer containing photoinitiator LAP, wherein the photoinitiator LAP is lithium phenyl-2,4,6-trimethylbenzoylphosphonate with a concentration of 1 mg / mL, to prepare a 10% (w / v) GeMA solution and a 5% (w / v) HA-CHO solution, respectively; Step S32, the mixing of the nanocomposite system, specifically involves mixing the above GeMA solution and HA-CHO solution at a volume ratio of 1:1, resulting in a final GeMA concentration of 5% and HA-CHO concentration of 2.5%, and adding 1 mg / mL of Arg-CDs stock solution; after mixing, the mixture is uniformly dispersed.
[0012] As a preferred embodiment: Step S33, photocrosslinking and gel formation, specifically involves irradiating the mixed solution in step S32 under ultraviolet light; the photoinitiator LAP is cleaved under ultraviolet light to generate free radicals, which initiate free radical chain polymerization between the methacrylate groups of the GeMA side chain, forming a first covalent crosslinking network.
[0013] As a preferred embodiment: Step S34, dynamic covalent crosslinking, specifically involves: simultaneously or after the photocrosslinking light in step S33, the aldehyde group on HA-CHO undergoes a Schiff base reaction with the remaining free amino group on the GeMA molecular chain to generate reversible imine bonds, constructing a second dynamic covalent crosslinking network, and finally obtaining a double-network composite hydrogel.
[0014] A composite hydrogel was prepared using the aforementioned preparation method.
[0015] An application of the composite hydrogel prepared by the preparation method described above, wherein the composite hydrogel is used to prepare a scaffold for repairing bone defects.
[0016] As a preferred embodiment: the bone defect is a skull defect; the composite hydrogel is used to promote the proliferation, migration and osteogenic differentiation of bone marrow mesenchymal stem cells.
[0017] Compared with existing technologies, this invention has significant advantages and beneficial effects. Specifically, as can be seen from the above technical solution, this invention uses L-arginine as a raw material to prepare Arg-CDs via pyrolysis, and uses hyaluronic acid as a raw material to prepare HA-CHO via sodium periodate oxidation. Then, using GelMA and HA-CHO as matrices, a double-network hydrogel is constructed through photocrosslinking and Schiff base reaction. The preparation method is simple to operate and the reaction conditions are mild, which can achieve efficient loading and controllable release of Arg-CDs and TGF-β1, and has good process repeatability and potential for large-scale production. The composite hydrogel of this invention can be used as a candidate scaffold material for bone defect repair, especially suitable for the repair of critical-sized skull defects, and has good clinical application prospects and translational potential.
[0018] To more clearly illustrate the structural features and effects of the present invention, a detailed description is provided below in conjunction with the accompanying drawings and specific embodiments. Attached Figure Description
[0019] Figure 1 These are electron micrographs and elemental diagrams of the simple hydrogel and carbon dots of the present invention; Figure 2 The images show physical photos, electron microscope images, and elemental diagrams of the composite hydrogel of this invention. Figure 3 This is a schematic diagram illustrating the physicochemical properties of the composite hydrogel of the present invention; Figure 4 This is a schematic diagram illustrating the cell compatibility and proliferation testing of the materials related to this invention. Figure 5 This is a schematic diagram illustrating how the materials of this invention promote cell migration; Figure 6 This is a schematic diagram illustrating the in vitro verification of the materials used in this invention to promote osteogenic cell formation. Figure 7 This is a schematic diagram illustrating the osteogenic verification of cranial defects in 4-week-old SD rats of the present invention. Figure 8 This is a schematic diagram illustrating the animal experiments on the promotion of bone regeneration in skull defects and the staining of tissue sections related to the materials of this invention. Figure 9 This is a schematic diagram illustrating the preparation, in vitro osteogenic activity, and in vivo bone regeneration and repair mechanism of the composite hydrogel of the present invention. Detailed Implementation
[0020] The present invention is as follows Figure 1 As shown in Figure 9, a method for preparing a composite hydrogel includes the following steps: Preparation of S1 and Arg-CDs: Arg-CDs were prepared by pyrolysis using L-arginine as a raw material; Preparation of S2 and HA-CHO: HA-CHO was obtained by oxidizing hyaluronic acid with sodium periodate, terminating the reaction, dialysis and freeze-drying. S3. Preparation of Arg-CDs / GelMA / HA-CHO composite hydrogel: S31. Preparation of precursor solution; S32. Mixing of nanocomposite system; S33. Photocrosslinking to form gel; S34. Dynamic covalent crosslinking.
[0021] Specifically, step S1 involves: heat-treating the arginine powder, cooling it, dissolving the residue in ultrapure water, sonicating the resulting turbid liquid, centrifuging it, and dialysis it; freezing and vacuum drying the dialysis solution to obtain powdered Arg-CDs.
[0022] The heat treatment conditions in step S1 are: calcination temperature 240℃, heating rate 4℃ / min, pyrolysis time 3 h; centrifugation conditions are: centrifugation at 15,000 r / min for 30 min at room temperature; the obtained powdered Arg-CDs are stored at 4℃.
[0023] Specifically, step S2 involves dissolving HA in deionized water, adding sodium periodate to the solution, and stirring for 2-3 hours. After the reaction is complete, ethylene glycol is added to terminate the reaction. After dialysis, the solution is freeze-dried to obtain HA-CHO.
[0024] Step S31, the preparation of the precursor solution, specifically involves adding methacrylamide gelatin (GeMA) and aldehyde-modified hyaluronic acid (HA-CHO) to a phosphate buffer containing the photoinitiator LAP. The photoinitiator LAP is lithium phenyl-2,4,6-trimethylbenzoylphosphonate with a concentration of 1 mg / mL, to prepare a 10% (w / v) GeMA solution and a 5% (w / v) HA-CHO solution, respectively. Step S32, the mixing of the nanocomposite system, specifically involves mixing the above GeMA solution and HA-CHO solution at a volume ratio of 1:1, resulting in a final GeMA concentration of 5% and a HA-CHO concentration of 2.5%, and adding 1 mg / mL of Arg-CDs stock solution; after mixing, the mixture is uniformly dispersed.
[0025] The specific steps of step S33, photocrosslinking and gel formation, are as follows: the mixed solution in step S32 is irradiated under ultraviolet light; the photoinitiator LAP is cleaved under ultraviolet light to generate free radicals, which initiate free radical chain polymerization between the methacrylate groups of the GeMA side chain to form the first covalent crosslinking network.
[0026] The specific steps of S34, dynamic covalent crosslinking, are as follows: simultaneously with or after the photocrosslinking light in step S33, the aldehyde group on HA-CHO undergoes a Schiff base reaction with the remaining free amino group on the GeMA molecular chain to generate reversible imine bonds, constructing a second dynamic covalent crosslinking network, and finally obtaining a double-network composite hydrogel.
[0027] A composite hydrogel was prepared using this method.
[0028] An application of the composite hydrogel prepared by this method is disclosed, wherein the composite hydrogel is used to prepare a scaffold for repairing bone defects.
[0029] The bone defect is a skull defect; the composite hydrogel is used to promote the proliferation, migration and osteogenic differentiation of bone marrow mesenchymal stem cells.
[0030] Example 1: A composite hydrogel, its preparation method and application Materials and Methods: Experimental reagents included: crystal violet (C0121, Beyotime), complete culture medium for rat bone marrow mesenchymal stem cells (STCC5011M, Sewell Biotech), BMSC cells (Zhongqiao Xinzhou), SD rats (Tenglai Biotechnology), 0.25% trypsin digestion solution (C0201, Beyotime), CCK-8 kit (C0038, Beyotime), and Calcein. AM / PI double staining kit (C2015S, Beyotime), pluripotent stem cell alkaline phosphatase staining kit (C3250S, Beyotime), Transwell chamber (725301, NEST), arginine (≥99%, Aladdin), hyaluronic acid (molecular weight: 100,000-200,000, Ron), sodium periodate (≥99.5%, Aladdin), ethylene glycol (≥99.8%, Aladdin), GelMA (≥99%, Aladdin), lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) (≥98%, Aladdin), PBS buffer (pH 7.4, Jizhi reagent), COL-1 antibody (Mitaka), OPN antibody (Mitaka), RUNX2 antibody (Mitaka).
[0031] The experimental instruments included: a fluorescence microscope (Ti2-U, Nikon), a CO2 constant temperature cell incubator (CellXpert® CS220, eppendorf), a centrifuge (Centrifuge 5420, eppendorf), a magnetic stirrer (FK-1, Fangke Instruments), a transmission electron microscope (FEI Tecnai G2 F20, FEI USA), an EDS energy dispersive spectroscopy analyzer (X-MaxN, Oxford, UK), a scanning electron microscope (ZEISS Sigma 300, Germany), a freeze dryer (ZLGJ-12, Huachen Kewangda Bio-instrument Technology Co., Ltd.), an X-ray photoelectron spectroscopy (Thermo Scientific K-Alpha, USA), a multi-functional microplate reader (Varioskan LUX, Thermo Fisher Scientific), a UV-Vis (UV3600, Shimadzu), an FTIR (IS50, USA), and a rheometer (HAAKE MARS60, Germany).
[0032] GelMA, hyaluronic acid, L-arginine, NaIO4, ethylene glycol, and photoinitiator LAP; recombinant TGF-β1; SD rat bone marrow mesenchymal stem cells (SD-rBMSCs) were purchased from Savill Biotechnology and maintained in culture using their complete rat bone marrow mesenchymal stem cell culture medium. α-MEM, DMEM, fetal bovine serum, penicillin-streptomycin solution, and CCK-8 reagent were also used. ALP staining kit, Alizarin Red staining kit, Calcein AM / PI live / dead cell staining kit, and COL-1, RUNX2, and OPN-related antibodies were also included.
[0033] Table 1: Group Naming
[0034] Table 2: Experimental Reagents
[0035] Table 3: Experimental Instruments
[0036] Table 4: Experimental Reagents
[0037] Table 5: Experimental Instruments
[0038] Material preparation and performance characterization: Preparation method of composite hydrogel: (1) Preparation of Arg-CDs Arg-CDs were prepared from L-arginine via pyrolysis. 500 mg of arginine powder was placed in a corundum crucible and heat-treated in a tube furnace at 240 °C, a heating rate of 4 °C / min, and a pyrolysis time of 3 h. After the tube furnace cooled naturally to room temperature, the residue was dissolved in 20 mL of ultrapure water. The resulting turbid solution was sonicated for 30 min, followed by centrifugation at 15,000 r / min for 30 min at room temperature. The supernatant was collected and dialyzed against ultrapure water for 24 h using a dialysis membrane (MWCO = 1000 Da), with the ultrapure water being replaced periodically. Finally, the dialyzed solution was frozen and vacuum-dried to obtain powdered Arg-CDs, which were stored at 4 °C.
[0039] (2) Preparation of HA-CHO Weigh 1.5 g of HA and add it to 150 mL of deionized water. Stir magnetically at room temperature until completely dissolved. Then add 802 mg of sodium periodate (NaIO4) to the solution and continue stirring for 2 h. After the reaction is complete, add 200 μL of ethylene glycol to terminate the reaction. Transfer the reaction solution to a dialysis bag, seal it, and dialyze it in deionized water for 48 h, changing the deionized water every 3 h. After dialysis, freeze-dry the solution to obtain HA-CHO, seal it, and store it at 4°C for later use.
[0040] (3) Preparation of Arg-CDs / GelMA / HA-CHO composite hydrogel Lyophilized GelMA and HA-CHO were dissolved in PBS containing photoinitiator LAP (1 mg / mL) to prepare precursor solutions of GelMA 10% (w / v) and HA-CHO 5% (w / v). When preparing the nanocomposite system, pre-prepared Arg-CDs (1 mg / mL) were added to the precursor solutions in proportion and sonicated or stirred to disperse them evenly. Subsequently, ultraviolet light irradiation was applied, and the photoinitiator generated free radicals to induce the polymerization of GelMA methacryloyl groups to construct a cross-linked network. At the same time, the aldehyde groups of HA-CHO reacted with the free amino groups of GelMA to form a second dynamic covalent cross-linked network.
[0041] The preparation method of Arg-CDs / GelMA / HA-CHO composite hydrogel is as follows: ① Preparation of precursor solutions: Lyophilized methacrylamide gelatin (GeMA) and aldehyde-modified hyaluronic acid (HA-CHO) were placed in sterile centrifuge tubes, and phosphate buffered saline (PBS, pH 7.4) containing photoinitiator LAP (lithium phenyl-2,4,6-trimethylbenzoylphosphonate, concentration 1 mg / mL) was added. The solutions were dissolved by shaking in a 37 ℃ water bath in the dark to obtain 10% (w / v) GeMA solution and 5% (w / v) HA-CHO solution, respectively. Intermittent vortexing can be used during the dissolution process to ensure complete dissolution and that the solution is clear and free of particles.
[0042] ② Mixing of the nanocomposite system: Mix the above GeMA solution and HA-CHO solution at a volume ratio of 1:1 (final GeMA concentration is 5%, HA-CHO concentration is 2.5%), and add the pre-ultrasonic dispersed Arg-CDs (arginine-modified carbon dots) stock solution (1 mg / mL) to achieve the designed final concentration in the mixed system (e.g., 50 μg / mL, 100 μg / mL, etc.). After mixing, use ice bath sonication (power 40 W, frequency 40 kHz, sonication for 2 s, pause for 3 s, total time 5 min) or magnetic stirring (300 rpm, 4 ℃, 10 min) to ensure uniform dispersion and avoid bubble generation.
[0043] ③ Photocrosslinking: The mixed solution is rapidly injected into a polytetrafluoroethylene mold (1 mm thick) and placed in an ultraviolet curing chamber (wavelength 365 nm, light intensity 10 mW / cm²) for 3–5 min (time can be adjusted according to preliminary experiments). The photoinitiator LAP cleaves under ultraviolet light to generate free radicals, which initiate free radical chain polymerization between the methacrylate groups on the GeMA side chains, forming the first covalent crosslinking network.
[0044] ④ Dynamic covalent crosslinking: During or after photocrosslinking (after standing at room temperature for 30 min), the aldehyde groups on HA-CHO react with the residual free amino groups on the GeMA molecular chain to form reversible imine bonds, constructing a second dynamic covalent crosslinking network, ultimately yielding a double-network composite hydrogel. After gelation, the gel is removed and washed three times with PBS (15 min each time) to remove unreacted monomers and residual photoinitiators.
[0045] Performance characterization of the composite hydrogel: (1) Detection of cross-sectional morphology of composite hydrogel The prepared composite hydrogel was adhered with conductive adhesive and sputtered with gold. Its cross-sectional morphology was observed by scanning electron microscopy (SEM). The distribution of C, O and N elements was observed by energy dispersive spectroscopy (EDS) mapping.
[0046] (2) Swelling and degradation test of GelMA / HA-CHO hydrogel The swelling test involved immersing the lyophilized hydrogel in PBS buffer at 37°C, removing it at predetermined time points, removing excess surface moisture, and weighing it. The water absorption ratio was calculated using the formula Swelling Ratio (%) = (Ws − Wd) / Wd × 100% (where Ws is the swelling equilibrium mass and Wd is the initial dry weight). The degradation test involved placing an equal volume of gel in PBS buffer at 37°C to simulate physiological degradation, periodically recording its residual mass, and characterizing its mass loss using the formula Degradation Rate (%) = (W0 − Wt) / W0 × 100% (where W0 is the initial mass and Wt is the mass at time t).
[0047] (3) TGF-β1 loading and in vitro release of composite hydrogel TGF-β1 was loaded at a concentration of 50 ng / mL into an Arg-CDs / GelMA / HA-CHO precursor solution, and then encapsulated within a three-dimensional network via a Schiff base reaction followed by UV crosslinking. One mL of the drug-loaded hydrogel was immersed in a constant-temperature (37°C) PBS buffer solution. At predetermined time points, 100 μL of the sample was collected and replenished with an equal volume of fresh medium. The drug concentration was determined by ELISA. The cumulative drug release formula is: Cumulative Release (%) = (C n (×V0 / Mdrug) × 100%. Cn is the concentration in the release medium at the nth sampling, V0 is the constant medium volume of 20 mL, and Mdrug is the initial total drug load of 50 ng.
[0048] Biocompatibility, proliferation, and cell migration properties of composite hydrogels were tested. Cell source and culture. SD-rBMSCs were purchased from Savill Biotechnology and cultured in a constant temperature incubator at 37℃, 5% CO2, and saturated humidity using their complete rat bone marrow mesenchymal stem cell culture medium. Cells in good condition at passage 2 (P2) were selected for subsequent experiments.
[0049] (1) Cell liveness / death staining (Calcein AM / PI) SD-rBMSCs were seeded in culture dishes. After cell adhesion, PBS (CON), G, GA, GT, and GAT (50 μg / mL) were added for co-incubation. Culture was terminated after 24 hours for detection. Old culture medium was aspirated, and cells were gently washed with PBS buffer. Then, prepared staining working solutions containing Calcein AM (green fluorescence, for live cells) and PI (red fluorescence, for dead cells) were added, and the cells were incubated at 37°C in a 5% CO2 incubator for 30 minutes in the dark. After staining, the cells were washed again with PBS to remove excess dye and immediately observed under a fluorescence microscope.
[0050] (2) Cell proliferation detection (CCK-8 assay) P2 generation SD-rBMSCs in logarithmic growth phase were seeded into 96-well plates at a density of 2000-4000 cells / well. Fresh culture medium containing 50 μg / mL GA or GAT was added to each well, and a blank control group (CON) was set up. The plates were incubated at 37℃ in a 5% CO2 incubator for 24, 72, and 120 hours, respectively. Afterward, the supernatant was carefully removed from each well, and 100 μL of fresh culture medium and 10 μL of CCK-8 solution were added to each well. The plates were then incubated in the dark for 1 hour. Finally, the absorbance of each well was measured at 450 nm using a microplate reader. Cell viability was calculated using the formula: Cell viability (%) = [(As-Ab) / (Ac-Ab)] × 100%, where As, Ac, and Ab represent the absorbance of the experimental group, the cell control group (CON), and the blank control group, respectively.
[0051] (3) Cell migration experiment Collect P2 generation SD-rBMSCs in the logarithmic growth phase, discard the culture medium, and wash once with PBS; digest with trypsin, and after the cells shrink and become rounded, add rat bone marrow mesenchymal stem cell complete culture medium to terminate digestion; centrifuge at 1000 rpm for 3 min, discard the supernatant; resuspend the cells in serum-free culture medium, thoroughly pipette to prepare a single-cell suspension and count the cells, adjusting the cell concentration to 2 × 10⁶ cells / mL. 5 cells / mL, 200 μL of cell suspension was seeded in each well of the upper chamber (total cells in the upper chamber 4 × 10⁶). 4(Number of cells). Remove the 24-well plate and add 600 μL of culture medium to the lower chamber to construct the culture system. Five groups were set up: CON, G, GA, GT, and GAT. The working final concentration of Arg-CDs was 50 μg / mL, and the working final concentration of TGF-β1 was 5 ng / mL. For the CON group, culture medium containing 10% FBS was added to the lower chamber. For the G group, a hydrogel substrate was pre-laid at the bottom of the wells, and then 10% FBS culture medium without drugs was added. For the other groups, the corresponding concentrations of Arg-CDs and TGF-β1 were added to the corresponding hydrogel substrate. The liquid surface should not touch the bottom of the chamber during addition to prevent air bubbles; if air bubbles are present, gently lift the chamber to remove them. Using sterile forceps, carefully place the Transwell chamber into the corresponding well of the 24-well plate, slowly add 200 μL of cell suspension to the upper chamber, and incubate at 37°C with 5% CO2 for 24 h. After culture, aspirate the liquid from both chambers. Gently rinse the upper and lower chambers once each with PBS. Gently wipe the surface of the upper membrane of each chamber with sterile cotton swabs to remove any unmigrated cells, repeating 2-3 times to avoid puncturing the polycarbonate membrane. Then immerse the chambers in 4% paraformaldehyde solution and fix at room temperature for 15-20 min. After washing twice with PBS, stain with 0.1% crystal violet solution at room temperature for 15 min. Rinse the chambers thoroughly with PBS until no purple precipitate appears in the rinse solution, and allow them to air dry at room temperature. Images were acquired using a 20× objective lens (scale bar 200 μm) under an inverted microscope. Three non-overlapping fields of view were randomly selected from each chamber, and the number of cells that had penetrated the membrane was counted using ImageJ software.
[0052] Osteogenic effects of composite hydrogels (1) ALP staining SD-rBMSC was used at 2×10⁻⁶ per well. 5 Cells were seeded in 6-well plates. After adhesion, the culture medium was replaced with osteogenic induction medium (α-MEM complete medium for the CON group), followed by PBS (OM group) and 50 μg / mL of each material group (G, GA, GT, GAT). ALP staining was performed 7 days after osteogenic induction. The culture medium in the wells was aspirated, and the cells were gently washed along the well walls 2-3 times with pre-cooled PBS for 1-2 min each time. The PBS was then aspirated. The cells were fixed with 4% paraformaldehyde (PFA) and incubated at room temperature for 15-20 min. The fixative was aspirated, and the cells were washed 3 times with PBS for 2 min each time. BCIP / NBT staining working solution was added until the cell layer was completely covered, and the cells were incubated at 37°C in the dark for 20 min. The color development was observed under a microscope, and grayscale quantitative analysis was performed.
[0053] (2) Alizarin Red staining 1×10 rats 4BMSCs were seeded in 24-well plates, with 500 μL of α-MEM complete medium added to each well. When the number of cells in the wells reached 70%-80% of the well area, the medium was aspirated, and 500 μL of fresh α-MEM complete medium (CON group), osteogenic induction medium (OM group), and corresponding extraction solutions were added to induce osteogenic growth. The medium was changed every 2-3 days. After 21 days of culture, the induced cells were stained with Alizarin Red. The specific steps are as follows: first, the medium was aspirated, washed 3 times with PBS, fixed with 4% paraformaldehyde for 40 min, the fixative was aspirated, washed 3 times with PBS, Alizarin Red staining solution was added to the wells, ensuring complete coverage of the sample, and stained for 3-5 min. Then, the staining solution was aspirated, washed 3 times with PBS, and then photographed under a microscope for quantitative analysis.
[0054] (3) Western Blot (protein immunoblotting) Rat bone marrow mesenchymal stem cells (BMSCs) were seeded in 6-well plates, with 2 mL of α-MEM complete medium added to each well. When the cell count reached 70%-80% of the well area, the medium was removed, and 2 mL of α-MEM complete medium (CON group), osteogenic induction medium (induction group), and corresponding extraction solutions were added to induce osteogenic growth. The medium was changed every 2-3 days. Cellular proteins were extracted at day 7, and the expression of osteogenic-related proteins COL-1, RUNX2, and OPN was detected, normalized using internal control proteins GAPDH or β-actin. Finally, the relative expression levels of the measured proteins were calculated and statistically analyzed.
[0055] Animal experiments: This study used male Sprague-Dawley rats (300–350 g) to establish a critical-sized skull defect model to evaluate the in vivo bone repair effect of composite hydrogels. All experimental procedures followed the National Institutes of Health (NIH) Guidelines for the Care and Use of Laboratory Animals and were approved by the Institutional Animal Care and Use Committee of Shihezi University (Approval No. A2025-936). The specific surgical procedure was as follows: First, the rats were anesthetized with sodium pentobarbital solution (Sigma-Aldrich), and then the scalp was disinfected. A longitudinal incision was made along the midline of the skull. Next, a critical-sized bone defect with a diameter of 5 mm was prepared on the skull, and the rats were randomly divided into 4 groups: CON group (bone defect prepared only, no material implanted), G group (GelMA / HA-CHO hydrogel only), GA group (hydrogel + Arg-CDs), and GAT group (hydrogel + Arg-CDs + TGF-β1), with n=5 in each group. The defect area was implanted in each group. Three specimens from each group were randomly selected at each postoperative time point for Micro-CT and histological analysis. Rats were sacrificed at weeks 4 and 8 postoperatively, and skull samples were collected. After fixation in 10% formalin, the following analyses were performed: Micro-CT scanning (SkyScan, Belgium) was used for three-dimensional reconstruction of the defect area and quantitative analysis of the new bone volume / tissue volume ratio (BV / TV); hematoxylin-eosin (H&E) staining and Masson's trichrome staining were used to observe the distribution of new bone tissue and collagen fibers.
[0056] Statistical methods: Data analysis in this study was performed using GraphPad Prism 8.0. Quantitative data are expressed as mean ± standard deviation (Mean ± SD). One-way ANOVA was used for comparisons among multiple groups, and Tukey's multiple comparison test was used for pairwise comparisons between groups. A p-value < 0.05 was considered statistically significant.
[0057] Discussion of Results: Electron micrographs of simple hydrogel and carbon dots: TEM images show that Arg-CDs are nearly spherical, uniformly dispersed, and have a relatively uniform particle size, with no obvious aggregation. SEM images show that the hydrogel cross-section exhibits a highly interconnected three-dimensional porous structure with good pore connectivity, suggesting that this structure may facilitate the expansion of specific surface area and provide diffusion channels for hydrophilic drugs or biomolecules. EDS mapping shows that C, O, and N elements are relatively uniformly distributed on the gel backbone, indicating that the components achieved good spatial distribution consistency during the cross-linking process. Figure 1 As shown.
[0058] Electron micrograph of the composite hydrogel: Images of Arg-CDs solution and the hydrogel formed by its composite with GelMA / HA-CHO are shown. Figure 2 As shown in Figure A, the gel does not flow when inverted, indicating the formation of a stable three-dimensional cross-linked network. UV-Vis absorption spectroscopy reveals new characteristic absorption peaks for Arg-CDs in the 250-300 nm range compared to the raw material arginine (Arg), suggesting successful carbon dot synthesis. SEM images show that the drug-loaded hydrogel retains its three-dimensional porous framework. Figure 2 As shown in Figure B, the pore size is approximately 50-100 μm, and the pore walls have good connectivity, similar to the unloaded system. EDS mapping results show that C, O, and N elements, representing carbon dots and the gel matrix, are relatively uniformly distributed on the porous framework, suggesting that the drug loading process did not lead to significant component aggregation. Figure 2 As shown.
[0059] Characterization of composite hydrogels: The C 1s spectrum exhibits characteristic peaks at 284.7 eV, 285.7 eV, and 288.0 eV, corresponding to the sp values of the carbon nucleus, respectively. 2 The hybrid carbon (CC / C=C) and surface functional groups CN / CO and C=N / C=O bonds; the N 1s spectrum is further subdivided into imine nitrogen (C=N) at 398.0 eV and amino / amide nitrogen (CN / NH) at 399.6 eV, confirming that the arginine precursor effectively integrates nitrogen into the carbon dot framework during nucleation; combined with the signal distributions of 531.1 eV (C=O) and 533.0 eV (C-OH) in the O 1s spectrum, it is jointly demonstrated that the carbon dot surface is rich in hydroxyl, carboxyl, and nitrogen-containing functional groups. These hydrophilic active sites not only endow Arg-CDs with excellent water dispersibility, but also provide the molecular structural basis for their stable integration with the GelMA / HA-CHO matrix through hydrogen bonding and dynamic covalent interactions, such as... Figure 3 As shown.
[0060] In FTIR spectroscopy analysis, the characteristic absorption peaks of each component clearly revealed the chemical integration and dynamic cross-linking process between materials. HA-CHO showed a peak at 1725 cm⁻¹. -1 The significant absorption peak appearing nearby is attributed to the stretching vibration of C=O in the aldehyde group (-CHO) generated by oxidation, confirming the successful functionalization of hyaluronic acid; in the composite hydrogel system, the weakening and shift of the aldehyde peak intensity is accompanied by the GelMA amide band (1645 cm⁻¹). -1 The enhanced signal strongly suggests that a dynamic covalent bond is formed between the amino and aldehyde groups via the Schiff base reaction. Furthermore, the introduction of Arg-CDs enhances the signal at 3300-3500 cm⁻¹. -1The broad -OH / -NH association peaks broadened and shifted, further reflecting the formation of a dense hydrogen bond network between the nano-carbon dots and the polymer matrix.
[0061] Rheological experiments showed that, across the entire angular frequency range, the storage modulus (G′) of all components was significantly higher than the loss modulus (G′′), exhibiting typical elastic solid behavior. The G′ of the Arg-CD / GelMA / HA-CHO composite gel was significantly higher than that of the pure GelMA / HA-CHO component, indicating that the nanocarbon dots acted as physical crosslinking points, enhancing the network structure and improving the mechanical strength of the material.
[0062] The swelling curves show that the hydrogel has excellent hydrophilicity and water retention capacity. Its swelling rate rapidly balances within 10 hours and eventually maintains around 600%. The degradation curves reflect the stability of the material under physiological conditions. The hydrogel initially exhibits slow degradation, but the degradation rate increases after 200 hours, which is consistent with the gradual hydrolysis process of the polymer network.
[0063] The GelMA / HA-CHO hydrogel exhibited a significant pH-responsive release characteristic for TGF-β1. Under neutral physiological conditions (pH 7.4), the hydrogel displayed ideal sustained-release behavior, with a smooth delivery process, gradually reaching a final release plateau of approximately 93% after about 120 hours. However, under simulated slightly acidic pathological conditions (pH 6.5), its release rate accelerated significantly, producing a noticeable burst release within the first 48 hours and rapidly releasing nearly 90% of the growth factor. This significant difference in rate indicates that the system can sensitively sense acidic microenvironments to achieve rapid, on-demand drug release, while maintaining good structural stability and long-lasting sustained-release effects under normal physiological conditions. Figure 3 As shown.
[0064] Cell biocompatibility and proliferation The results of live / dead cell staining (Calcein AM / PI) showed that, as Figure 4 As shown in Figure B, a large number of green live cells and very few red dead cells were visible in each group of fields of view, indicating that the tested material had low cytotoxicity at the experimental concentration. CCK-8 proliferation results showed that... Figure 4As shown in Figure A, cell viability continuously increased with prolonged culture time (24-120 h). Using the CON group as the baseline (100%), the cell viability of the GA group at 24, 72, and 120 h were 103.7%±0.3%, 109.8%±1.3%, and 110.2%±0.3%, respectively; while those of the GAT group were 110.0%±1.5%, 125.2%±1.1%, and 129.7%±1.1%, respectively. The cell viability of the GAT group was higher than that of the GA group at all time points, suggesting that the combined application of Arg-CDs and TGF-β1 has a better promoting effect on cell proliferation than Arg-CDs alone. Further statistical testing (such as interaction terms in two-way ANOVA) is needed to confirm the specific interaction effect.
[0065] Cell migration experiment: Transwell cell migration assay results showed that, Figure 5 As shown, the number of cells that migrated through the membrane in each group (cells / field, mean ± standard deviation) were: CON, 108.3 ± 15.9; G, 112.3 ± 11.7; GA, 148.3 ± 8.7; GT, 212.7 ± 3.5; and GAT, 348.3 ± 21.6. There was no statistically significant difference between the CON and G groups (P > 0.05); the number of cells that migrated through the membrane in the GT group was significantly higher than that in the G group (P < 0.0001); and the number of cells that migrated through the membrane in the GAT group was the highest, significantly higher than that in the GT group (P < 0.0001) and the G group (P < 0.0001). These results suggest that the GAT complex system has a better promoting effect on cell migration than any of the individual treatment groups.
[0066] In vitro osteogenic validation: The results of alkaline phosphatase staining and quantification (with the CON group as 1.00) showed that, as Figure 6 As shown, CON, 1.00±0.36; OM, 4.60±0.83; G, 4.67±1.65 (P > 0.99 compared with OM, no statistical difference); GA, 9.76±0.62 (P = 0.018 compared with G group); GT, 9.37±1.92 (P = 0.030 compared with G group); GAT, 16.13±2.67, significantly higher than GA group (P = 0.0021) and GT group (P = 0.0034). These results suggest that the combined application of GA and TGF-β1 has a better promoting effect on early osteogenic differentiation than either treatment alone.
[0067] Quantitative results of alizarin red staining (with the CON group as 1.00-fold) showed that OM, 13.22±3.99; G, 18.75±0.18; GA, 24.22±1.29 (compared to the G group, P < 0.0001); GT, 25.74±1.80; GAT, 29.25±1.00, were significantly higher than those in the GA group (P = 0.010) and the GT group (P = 0.006). These results suggest that the combined application of GA and TGF-β1 has a better promoting effect on late-stage osteogenic mineralization than either of them alone.
[0068] Western blot and quantitative analysis results showed (relative expression levels normalized to 1.00 for the CON group) that, compared with the CON group, the expression of COL-1 (1.82±0.22, P = 0.22), RUNX2 (1.06±0.06, P = 0.22), and OPN (1.04±0.01, P = 0.48) in the G group showed no significant changes, suggesting that the basic gel material itself has limited direct promoting effect on osteogenic differentiation. The expression of all three proteins in the GA group was significantly upregulated compared with the CON group (COL-1, 4.15±0.56, P < 0.001; RUNX2, 1.22±0.02, P < 0.001). The expression levels of COL-1 (5.68±0.55), RUNX2 (1.40±0.08), and OPN (1.79±0.26) in the GAT group (Arg-CDs and TGF-β1 combined treatment) were significantly upregulated compared to the CON group (COL-1, P = 0.01; RUNX2, P = 0.004; OPN, P = 0.004) and the GT group (COL-1, P = 0.09). This suggests that TGF-β1 alone can effectively induce osteogenic differentiation. The expression of the three proteins was significantly different between the GA and GT groups (P>0.05). These results suggest that the combined application of these two methods promotes osteogenic differentiation at the protein level more effectively than either method alone.
[0069] In vivo osteogenic validation in SD rats: The in vivo experiments consisted of four groups: CON (defect only, no implanted material), G, GA, and GAT (GT group not included in the in vivo study). Four weeks post-surgery, Micro-CT 3D reconstruction showed... Figure 7As shown in Figure A, in group CON, no significant new bone formation was observed in the critical-sized skull defect area; the bone defect margins were clear and unhealed. In group G, a small amount of new bone tissue was visible filling the defect area, but a large bone defect gap remained in the center. New bone formation was increased in group GA compared to group G. Group GAT had the most abundant new bone tissue, with almost complete healing of the bone defect and good restoration of cortical continuity. HE staining further showed that... Figure 8 As shown in Figure A, the defect area in group CON was mainly filled with fibrous connective tissue, with no obvious new bone formation. In group G, a small amount of newly formed woven bone was visible at the edge of the defect area, while the central area was predominantly fibrous tissue. New bone formation was more abundant in group GA than in group G. Group GAT showed the densest new bone formation, with regularly arranged trabeculae and mature lamellar bone structure, indicating that the bone defect had essentially achieved bony healing. Masson trichrome staining showed... Figure 8 As shown in Figure B, the defect area in group CON was mainly composed of blue-stained collagen fibers, with no obvious mineralized bone matrix. In group G, a small amount of red-stained mineralized bone tissue was distributed at the defect edge. The mineralized bone tissue in group GA was more abundant than in group G. Group GAT had the richest mineralized bone tissue, with a wide distribution of red-stained areas, high bone matrix maturity, and orderly collagen arrangement. (HE and Masson staining were qualitative observations; quantitative analysis of the staining results was not performed in this study.) Quantitative analysis of BV / TV and Tb.N showed that, as Figure 7 China B and Figure 7 As shown in Figure C, at 4 weeks, the bone volume fractions (mean ± standard deviation, %) of each group were as follows: CON, 14.43 ± 0.71; G, 15.02 ± 0.74; GA, 18.85 ± 0.44; GAT, 21.01 ± 0.86. There was no statistically significant difference between the CON and G groups (P = 0.75). The BV / TV ratio in the GA group was significantly higher than that in the G group (P < 0.001). The BV / TV ratio in the GAT group was the highest, significantly higher than that in the GA group (P = 0.02), the G group (P < 0.001), and the CON group (P < 0.001), suggesting that the GAT composite system showed superior bone induction activity compared to the GA and G groups at 4 weeks postoperatively.
[0070] Eight weeks post-surgery, Micro-CT three-dimensional reconstruction showed a similar but more pronounced trend to that at four weeks, such as... Figure 7 As shown in Figure D, no significant new bone formation was observed in the critical-sized skull defect area of group CON, and the bone defect did not heal; a small amount of new bone tissue was visible in group G, but a large gap remained in the center of the defect; new bone formation was further increased in group GA compared to group G; group GAT had the most abundant new bone formation, the bone defect was almost completely healed, and the continuity of the bone cortex was well restored. HE staining showed that, as Figure 8As shown in Figure C, the defect area in group CON is mainly filled with fibrous connective tissue; a small amount of woven bone is visible at the edge in group G; the trabecular bone structure is initially formed in group GA; and a regularly arranged mature lamellar bone structure is visible in group GAT, indicating that bony healing has been basically achieved. Masson trichrome staining shows that... Figure 8 As shown in Figure D, the content of mineralized bone matrix in each group increases sequentially, with the GAT group exhibiting the most extensive red-stained area and the highest bone matrix maturity. Quantitative analysis of BV / TV and Tb.N showed that, as Figure 7 China E and Figure 7 As shown in Figure F, at 8 weeks, the bone volume fractions (mean ± standard deviation, %) of each group were: CON, 18.20 ± 1.00; G, 18.85 ± 0.72; GA, 30.74 ± 1.09; and GAT, 34.12 ± 1.69. There was no statistically significant difference between the CON and G groups (P = 0.90). The BV / TV ratio in the GA group was significantly higher than that in the G group (P < 0.001). The GAT group had the highest BV / TV ratio, significantly higher than the GA group (P = 0.03), the G group (P < 0.001), and the CON group (P < 0.001). This suggests that the GAT composite system maintained superior bone induction activity compared to the GA and G groups at 8 weeks post-surgery, and its bone repair advantage was maintained and further consolidated during weeks 4 to 8.
[0071] This application constructs a GelMA / HA-CHO composite hydrogel system (GAT) loaded with Arg-CDs and TGF-β1, and systematically evaluates its in vitro osteogenic activity and in vivo bone regeneration and repair effects. Experimental results show that the GAT composite hydrogel has a better promoting effect on the proliferation, migration, and osteogenic differentiation of BMSCs than hydrogel treatment alone or Arg-CDs and TGF-β1 loading treatment alone, and achieves effective bone repair in a critical-size skull defect model in SD rats.
[0072] The microstructure of hydrogel scaffolds is a key factor determining their biological properties. The GAT composite hydrogel prepared in this study exhibits a highly interconnected three-dimensional porous network structure with pore sizes ranging from 50 to 100 μm, consistent with the porosity characteristics of the extracellular matrix of natural bone tissue. This facilitates nutrient permeation, metabolic waste removal, and cell adhesion and ingrowth. Scanning electron microscopy and energy dispersive spectroscopy (EDS) analyses confirmed that Arg-CDs were uniformly dispersed within the GelMA / HA-CHO polymer network, without significant phase separation or aggregation. Rheological results showed that the introduction of Arg-CDs significantly enhanced the storage modulus of the hydrogel, indicating that the nanocarbon dots, acting as physical crosslinking points, effectively strengthened the mechanical strength of the network structure. This is related to the hydrogen bonds and dynamic covalent interactions formed between the abundant hydroxyl, carboxyl, and amino functional groups on the carbon dot surface and the polymer matrix. Furthermore, this hydrogel exhibits controllable swelling and degradation behavior in a physiological environment. Its slow degradation rate ensures continuous mechanical support in the early stages of bone repair, gradually diminishing as new bone tissue forms, matching the bone regeneration process.
[0073] Arg-CDs play a dual role in this composite system. On the one hand, as a nanocarrier, the abundant functional groups on the surface of Arg-CDs can effectively load TGF-β1 through electrostatic adsorption and hydrogen bonding, forming a stable Arg-CDs / TGF-β1 complex. On the other hand, Arg-CDs themselves retain the biological activity of L-arginine, and the NO produced by its metabolism can promote the proliferation and differentiation of osteoblasts through the NO signaling pathway. In this study, the incorporation of Arg-CDs endowed the hydrogel with good antioxidant properties, which is of great significance for alleviating the oxidative stress state in the local microenvironment of bone defects and protecting cells from reactive oxygen species damage. In vitro release experiments showed that TGF-β1 from GAT hydrogel exhibited a biphasic kinetic characteristic of rapid release followed by steady sustained release. The early rapid release is conducive to quickly reaching the therapeutic concentration to initiate the osteogenic signaling cascade, while the later sustained release maintains the long-term biological effect, avoiding the drawback of rapid inactivation of growth factors in traditional direct drug delivery methods.
[0074] Cell compatibility is a primary indicator for evaluating the application potential of biomaterials. Live and dead cell staining and CCK-8 proliferation assays confirmed that the GAT composite hydrogel exhibits good biocompatibility, did not show significant toxicity to BMSCs, and even promoted cell proliferation. This result is consistent with the good biocompatibility of GelMA and HA-CHO themselves, and also suggests that Arg-CDs and TGF-β1 have good cellular safety within the experimental concentration range.
[0075] Cell migration is a crucial step in the recruitment of bone mesenchymal stem cells (BMSCs) to bone defects during bone regeneration. Transwell migration assays showed that TGF-β1 loading enhanced the transmembrane migration ability of BMSCs, consistent with the known mechanism by which TGF-β1, as a chemokine, activates the Smad2 / 3 signaling pathway, promotes cytoskeleton remodeling, and induces pseudopodia formation. While Arg-CDs alone had limited effect on promoting cell migration, their combined application with TGF-β1 resulted in a higher number of migrating cells in the GAT group compared to the individual treatment groups. This suggests that Arg-CDs may enhance the chemotactic effect of TGF-β1 by improving material surface properties or participating in related signaling pathways; the specific mechanism requires further investigation.
[0076] Osteogenic differentiation capacity is a core indicator for evaluating the functionality of bone repair materials. ALP, as an early marker enzyme in osteogenic processes, reflects the initial ability of cells to differentiate into an osteogenic phenotype; Alizarin Red staining reveals calcium nodule formation, representing the maturity of late-stage osteogenic mineralization. In this application, the GAT group showed superior ALP activity and the number of mineralized nodules compared to the control groups and single-treatment groups, suggesting that the combined application of Arg-CDs and TGF-β1 can promote the osteogenic process of BMSCs from both early and late stages of osteogenic differentiation. Western blot results further supported this conclusion at the protein level, with upregulated expression levels of osteogenic markers such as COL-1, RUNX2, and OPN in the GAT group. COL-1, as the most abundant organic component of the bone matrix, provides a scaffold template for subsequent mineralization deposition; RUNX2, as a master transcription factor controlling osteogenic differentiation, regulates the expression of various downstream osteogenic-related genes; and OPN participates in the mineralization regulation of the bone matrix and the interaction between osteocytes and the matrix. The above results collectively suggest that GAT composite hydrogels promote the osteogenic process of BMSCs from both the early and late stages of osteogenic differentiation.
[0077] In vivo experiments further validated the bone repair efficacy of the GAT composite hydrogel. In a rat model of critical-size skull defects, Micro-CT, histological, and quantitative analyses at 4 and 8 weeks post-surgery showed a consistent trend: the GAT group exhibited the most significant bone regeneration, with the largest amount and highest maturity of newly formed bone tissue, and the bone defect was essentially completely healed. Notably, at the relatively early observation point of 4 weeks post-surgery, the GAT group already showed a significant bone induction advantage, suggesting that this composite system can initiate the bone regeneration process earlier; by 8 weeks post-surgery, its bone repair effect was further consolidated, and the continuity of the bone cortex was well restored. In contrast, the bone regeneration effect of the hydrogel-only group (G group) was limited, with no statistically significant difference compared to the blank control group, suggesting that although the hydrogel matrix alone can provide physical support, its biological activity is insufficient to effectively induce bone regeneration. The GA group showed some osteogenic effect, but not as much as the GAT group, suggesting that the combined application of Arg-CDs and TGF-β1 has a better promoting effect on bone repair than Arg-CDs alone.
[0078] This application successfully constructed a GelMA / HA-CHO composite hydrogel (GAT) loaded with Arg-CDs and TGF-β1. This material possesses an interconnected porous network structure, good viscoelasticity and cell compatibility, and can achieve rapid initial release and subsequent sustained release of TGF-β1 in vitro. In vitro experiments showed that the GAT composite hydrogel more effectively promoted the proliferation, migration, and osteogenic differentiation of BMSCs than single-component treatments; in vivo experiments further demonstrated that this material can improve new bone formation in critical-size defects of the rat skull, with better results than the single-component treatment group.
[0079] This application aims to construct a GelMA / HA-CHO composite hydrogel loaded with arginine-derived carbon dots (Arg-CDs) and transforming growth factor-β1 (TGF-β1), and to evaluate its physicochemical properties and osteogenic potential.
[0080] Composite hydrogels were prepared using methacrylamide gelatin (GelMA) and aldehyde-modified hyaluronic acid (HA-CHO) as substrates via photocrosslinking and Schiff base reaction. Arg-CDs were synthesized using L-arginine as a precursor and co-loaded with TGF-β1 into the hydrogel system. The morphology, chemical structure, and viscoelasticity of the hydrogels were characterized by scanning electron microscopy, spectroscopy, and rheology. The release behavior of TGF-β1 was evaluated through in vitro release experiments. Using rat bone marrow mesenchymal stem cells (BMSCs) as a model, the effects of the hydrogels on cell activity, proliferation, migration, and osteogenic differentiation were investigated. The in vivo bone repair effect was also evaluated in a rat model of critical-size skull defects.
[0081] The composite hydrogel possesses an interconnected porous structure and good viscoelasticity. Arg-CDs are more uniformly distributed within the hydrogel network, resulting in a higher storage modulus compared to the simple hydrogel. TGF-β1 exhibits a rapid early release followed by a gradual slowdown in vitro, with a cumulative release rate of approximately 90% after 120 hours. Compared to the blank hydrogel and single-component treatment groups, the Arg-CDs and TGF-β1 combined (GAT) group showed higher BMSC proliferation levels at all time points (e.g., 129.7% at 120 h compared to 110.2% in the GA group), the highest number of migrating cells (348.3 / field, compared to 148.3 in the GA group and 212.7 in the GT group), and was superior to each individual treatment group in ALP activity, mineralized nodule formation, and expression of osteogenic-related proteins such as COL-1, RUNX2, and OPN. In a rat model of skull defects, the BV / TV in the GAT group was significantly higher than that in the GA group (18.85%±0.44%; 30.74%±1.09%), the hydrogel group (15.02%±0.74%; 18.85%±0.72%), and the blank control group (14.43%±0.71%; 18.20%±1.00%) at 4 weeks (21.01%±0.86%) and 8 weeks (34.12%±1.69%) after surgery.
[0082] The GelMA / HA-CHO composite hydrogel loaded with Arg-CDs and TGF-β1 exhibits excellent physicochemical properties, cell compatibility, and in vitro and in vivo osteogenic activity, showing superior effects compared to any single component treatment. These results support the hydrogel as a candidate scaffold for bone defect repair; however, its mechanism of action and long-term in vivo safety require further validation before clinical translation can be considered.
[0083] The key design feature of this invention is that it uses L-arginine as a raw material to prepare Arg-CDs via pyrolysis, and hyaluronic acid as a raw material to prepare HA-CHO via sodium periodate oxidation. Then, using GelMA and HA-CHO as matrices, a dual-network hydrogel is constructed through photocrosslinking and Schiff base reaction. The preparation method is simple to operate and the reaction conditions are mild, enabling efficient loading and controlled release of Arg-CDs and TGF-β1. It has good process reproducibility and potential for large-scale production. The composite hydrogel of this invention can serve as a candidate scaffold material for bone defect repair, especially suitable for the repair of critical-sized skull defects, and has good clinical application prospects and translational potential.
[0084] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the technical scope of the present invention. Therefore, any minor modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite hydrogel, characterized in that: Includes the following steps: Preparation of S1 and Arg-CDs: Arg-CDs were prepared by pyrolysis using L-arginine as a raw material; Preparation of S2 and HA-CHO: HA-CHO was obtained by oxidizing hyaluronic acid with sodium periodate, terminating the reaction, dialysis and freeze-drying. S3. Preparation of Arg-CDs / GelMA / HA-CHO composite hydrogel: S31. Preparation of precursor solution; S32. Mixing of nanocomposite system; S33. Photocrosslinking to form gel; S34. Dynamic covalent crosslinking.
2. The preparation method according to claim 1, characterized in that: Step S1 specifically involves: heat-treating the arginine powder, cooling it, dissolving the residue in ultrapure water, sonicating the resulting turbid liquid, centrifuging it, and dialysis it; freezing and vacuum drying the dialysis solution to obtain powdered Arg-CDs.
3. The preparation method according to claim 2, characterized in that: The heat treatment conditions in step S1 are: calcination temperature 240℃, heating rate 4℃ / min, pyrolysis time 3 h; centrifugation conditions are: centrifugation at 15,000 r / min for 30 min at room temperature; and the obtained powdered Arg-CDs are stored at 4℃.
4. The preparation method according to claim 1, characterized in that: Step S2 specifically involves: dissolving HA in deionized water, adding sodium periodate to the solution, and stirring the reaction for 2-3 hours; after the reaction is complete, adding ethylene glycol to terminate the reaction; and after dialysis, freeze-drying the solution to obtain HA-CHO.
5. The preparation method according to claim 1, characterized in that: Step S31, the preparation of the precursor solution, specifically involves adding methacrylamide gelatin (GeMA) and aldehyde-modified hyaluronic acid (HA-CHO) to a phosphate buffer containing the photoinitiator LAP. The photoinitiator LAP is lithium phenyl-2,4,6-trimethylbenzoylphosphonate with a concentration of 1 mg / mL, to prepare a 10% (w / v) GeMA solution and a 5% (w / v) HA-CHO solution, respectively. Step S32, the mixing of the nanocomposite system, specifically involves mixing the above GeMA solution and HA-CHO solution at a volume ratio of 1:1, resulting in a final GeMA concentration of 5% and a HA-CHO concentration of 2.5%, and adding 1 mg / mL of Arg-CDs stock solution. After mixing, the mixture is uniformly dispersed.
6. The preparation method according to claim 1, characterized in that: The step S33, photocrosslinking and gel formation, specifically involves irradiating the mixed solution from step S32 under ultraviolet light; the photoinitiator LAP is cleaved under ultraviolet light to generate free radicals, which initiate free radical chain polymerization between the methacrylate groups of the GeMA side chain, forming a first covalent crosslinking network.
7. The preparation method according to claim 1, characterized in that: The specific steps of S34, dynamic covalent crosslinking, are as follows: simultaneously with or after the photocrosslinking light in step S33, the aldehyde group on HA-CHO reacts with the residual free amino group on the GeMA molecular chain to generate reversible imine bonds, constructing a second dynamic covalent crosslinking network, and finally obtaining a double-network composite hydrogel.
8. A composite hydrogel, characterized in that: It is prepared by the preparation method described in any one of claims 1-7.
9. An application of a composite hydrogel prepared by the preparation method according to any one of claims 1-7, characterized in that: The composite hydrogel is used to prepare a scaffold for repairing bone defects.
10. The application according to claim 9, characterized in that: The bone defect is a skull defect; the composite hydrogel is used to promote the proliferation, migration and osteogenic differentiation of bone marrow mesenchymal stem cells.
